2022
DOI: 10.1101/2022.01.02.22268601
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Natural history and epidemiology of cleft lip and palate: a registry-based study in Iran (2000-19)

Abstract: The aim of this study was to provide the natural history and epidemiology of cleft lip and cleft palate in the northwest region of Iran between 2000 and 2019. Since 2000, infants born with birth defects have been registered in the Tabriz Registry of Congenital Anomalies (TRoCA). For this study, the information and data were collected using the TRoCA registry system. Prevalence of cleft lip and cleft palate was 1.48 (95% CI 1.34; 1.62) per 1000 live births over the past two decades in the region. The occurrence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Research by Galeh et al (2020) in Iran showed result about 20.86% patient with cleft has family history with cleft lip or palate. 1 Other study was in Saudi arabia that reported there were 4 patient (25%) that has family history with cleft lip or palate. 5,14 This result explained that orofacial cleft is known to have an increased frequency in relatives of family members with a cleft.…”
Section: Accompanying Syndromesmentioning
confidence: 97%
See 1 more Smart Citation
“…Research by Galeh et al (2020) in Iran showed result about 20.86% patient with cleft has family history with cleft lip or palate. 1 Other study was in Saudi arabia that reported there were 4 patient (25%) that has family history with cleft lip or palate. 5,14 This result explained that orofacial cleft is known to have an increased frequency in relatives of family members with a cleft.…”
Section: Accompanying Syndromesmentioning
confidence: 97%
“…Cleft lip with or without cleft palate are the most common congenital anomalies affecting the head and neck and the second most common congenital abnormalities in general. 1 Previous study explained that in New Haven, Connecticut cleft palate incidence is about 1 per 1593 live births. 2 Cleft palate occurs congenitally from failure of palatal shelf fusion.…”
Section: Introductionmentioning
confidence: 99%